Allyl-isothiocyanate treatment induces a complex transcriptional reprogramming including heat stress, oxidative stress and plant defence responses in Arabidopsis thaliana. (December 2016) - Kissen, Ralph; Øverby, Anders; Winge, Per; Bones, Atle
Abstract Background Isothiocyanates (ITCs) are degradation products of the plant secondary metabolites glucosinolates (GSLs) and are known to affect human health as well as plant herbivores and pathogens. To investigate the processes engaged in plants upon exposure to isothiocyanate we performed a genome scale transcriptional profiling ofArabidopsis thaliana at different time points in response to an exogenous treatment with allyl-isothiocyanate. Results The treatment triggered a substantial response with the expression of 431 genes affected (P < 0.05 and log2 ≥ 1 or ≤ -1) already after 30 min and that of 3915 genes affected after 9 h of exposure, most of the affected genes being upregulated. These are involved in a considerable number of different biological processes, some of which are described in detail: glucosinolate metabolism, sulphate uptake and assimilation, heat stress response, oxidative stress response, elicitor perception, plant defence and cell death mechanisms. Conclusion Exposure ofArabidopsis thaliana to vapours of allyl-isothiocyanate triggered a rapid and substantial transcriptional response affecting numerous biological processes. These include multiple stress stimuli such as heat stress response and oxidative stress response, cell death and sulphur secondary defence metabolism. Hence, effects of isothiocyanates on plants previously reported in the literature were found to be regulated at the gene expression level. This opens some avenues for further investigations to decipher the molecular mechanisms underlying the effects of isothiocyanates on plants.